КОНЦЕПЦИЯ ГЕОМОРФОЛОГИЧЕСКИХ ФОРМАЦИЙ И ПУТИ ЕЕ РАЗВИТИЯ - Лопатин Д.В. (My University, 2005)
The relief of depressions and ridges in the alpine type middle mountains of Pribaikal'e was analyzed in the context of N.A. Florensov's concept of geomorphologic formations. Author aimed to develop a new doctrine, which would be able to overcome the one-sidedness of geomorphology.
Keywords: 551.4.011